2003
DOI: 10.1079/bjn2002775
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vitamin C deficiency with food restriction on collagen cross-link ratios in bone, urine and skin of weanling guinea-pigs

Abstract: Mild-to-moderate vitamin C depletion in weanling guinea-pigs affects pyridinoline:deoxypyridinoline (collagen cross-link) ratios in femur shaft and urine, attributed to impairment of hydroxylation of collagen lysine. We investigated: (1) whether the picture at two time points is compatible with progressive accumulation of abnormal collagen; (2) whether any changes are seen in skin, where little deoxypyridinoline occurs; (3) whether total food restriction has similar effects. Male weanling Dunkin-Hartley guinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Independent of its effects on hydroxylation, ascorbate may stimulate collagen synthesis (Geesin et al , ; Sullivan et al , ). Collagen synthesis may be decreased in scorbutic animals (Peterkofsky, ; Kipp et al , ; Tsuchiya and Bates, ). Reduced collagen cross‐links may be a marker of vitamin C deficiency in the guinea pig (Tsuchiya and Bates, ) but this may not be specific to vitamin C deficiency.…”
Section: Known and Postulated Actions Of Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of its effects on hydroxylation, ascorbate may stimulate collagen synthesis (Geesin et al , ; Sullivan et al , ). Collagen synthesis may be decreased in scorbutic animals (Peterkofsky, ; Kipp et al , ; Tsuchiya and Bates, ). Reduced collagen cross‐links may be a marker of vitamin C deficiency in the guinea pig (Tsuchiya and Bates, ) but this may not be specific to vitamin C deficiency.…”
Section: Known and Postulated Actions Of Vitamin Cmentioning
confidence: 99%
“…Collagen synthesis may be decreased in scorbutic animals (Peterkofsky, 1991;Kipp et al, 1996;Tsuchiya and Bates, 2003). Reduced collagen cross-links may be a marker of vitamin C deficiency in the guinea pig (Tsuchiya and Bates, 2003) but this may not be specific to vitamin C deficiency. Although many features of human scurvy appear to be due to weakening of connective tissue, it has not been shown that these lesions are due to defective collagen synthesis.…”
Section: Collagen Hydroxylationmentioning
confidence: 99%
“…Evidence that optimal vitamin C status may be critical for optimal pyridinium cross-link formation, which in turn may be reflected uniquely by the cross-link ratio pyridinoline:deoxypyridinoline in bone collagen and in the urinary collagen degradation products of bone turnover, has been obtained from two sources. The first was a series of controlled vitamin C intake studies on guinea-pigs, which, like man, are totally dependent on dietary sources of vitamin C. In weanling guinea-pigs, following a wide range of vitamin C intakes and with a correspondingly wide range of tissue vitamin C concentrations, the pyridinoline: deoxypyridinoline cross-link ratio in the long bones and in urinary collagen degradation products were both highly sensitive to the vitamin C supply (Tsuchiya & Bates, 1997, 1998, 2003Bates, 1999). This dependence of the cross-link ratios on vitamin C was specific, insofar that it was not significantly affected by total food restriction (Tsuchiya & Bates, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a shift in collagen cross-link patterns, away from a preponderance of the hydroxylysyl -pyridinoline (here called pyridinoline) cross-link-type, towards the alternative lysyl -pyridinoline (here called deoxypyridinoline) one, which requires one less hydroxylysyl residue since it is replaced by a lysyl residue (Robins, 1994;Bailey et al 1998). Such an alteration in cross-link pattern, potentially the result of a mild dietary vitamin C deficiency, has been demonstrated in guinea-pigs (Tsuchiya & Bates, 1997, 1998, 2003 and in human subjects with the genetic disorder Ehlers -Danlos syndrome type VI. In the latter, a structurally altered lysyl hydroxylase enzyme requires abnormally large amounts of vitamin C in order to achieve partially adequate function (Pinnell et al 1972;Quinn & Krane, 1976;Miller et al 1979;Acil et al 1995).…”
mentioning
confidence: 99%
“…The observation of guinea pigs has appointed the bone tissue as the second most vulnerable to VC deficiency organ [21], which was associated with improper collagen synthesis. Severe vitamin C deficiency inhibited animal growth [22] and was associated with a significant change in collagen composition, namely deoxypyridinoline and the pyridinoline: eoxypyridinoline ratio in the femur shaft [23]. Bone mineral content and density has also been shown to decrease in scorbutic guinea pigs, paired by a thinner growth plate and larger osteoclast surface and impaired collagen synthesis at articular cartilage and tendons [24].…”
Section: Studies On Animal Modelsmentioning
confidence: 99%